(untitled) (Research, Society and Development, 2021)
This study aims to analyze the profile of pulmonary mechanics in patients who developed the severe form of COVID-19 and were hospitalized in an ICU in the southern interior of the state of Rondônia. This is a field study with a quantitative, cross-sectional descriptive, documentary, retrospective and prospective exploratory approach by analyzing secondary information from medical, nursing and physiotherapy records about demographic data, epidemiological, therapeutic, and clinical outcome of patients with positive RT-PCR for SARS-CoV-2 treated with MV within the first six months of pandemic care. Seventy samples were grouped, of which 57.14% were male with a mean age of 63.06 ± 14.95 years, height of 166.1 ± 9.09 cm and PBW of 60.54 ± 9.78 kg. The most common comorbidities were, SAH (61.43%), obesity (38.57%), DM (32.86%) and heart disease (15.71%). As for pulmonary mechanics, mean values of Total PEEP were found 8.24 + 0.58 cmH2O, Cst 30.42 + 10.07 ml/cmH2O, Pplateau 19.93 + 3.43 cmH2O, Rwa 13.56 + 5.44 cmH2O /Ls and SD of 11.82 + 3.47. It was observed in this sample that patients with ARDS secondary to COVID-19 had pulmonary mechanics similar to classic ARDS, with no differentiation of phenotypes or pattern in mechanics that would indicate a probability of clinical outcome (discharge/death) among patients.